Variation in Resistance to Hydrostatic Pressure among Strains of Food-Borne Pathogens - Alpas, H. (American Society for Microbiology, 1999)
Among food-borne pathogens, some strains could be resistant to hydrostatic pressure treatment. This information is necessary to establish processing parameters to ensure safety of pressure-pasteurized foods (N. Kalchayanand, A. Sikes, C. P. Dunne, and B. Ray, J. Food Prot. 61:425–431, 1998). We studied variation in pressure resistance among strains of Listeria monocytogenes, Staphylococcus aureus, Escherichia coli O157:H7, and Salmonella species at two temperatures of pressurization. Early-stationary-phase cells in 1% peptone solution were pressurized at 345 MPa either for 5 min at 25°C or for 5, 10, or 15 min at 50°C. The viability loss (in log cycles) following pressurization at 25°C ranged from 0.9 to 3.5 among nine L. monocytogenes strains, 0.7 to 7.8 among seven S. aureus strains, 2.8 to 5.6 among six E. coli O157:H7 strains, and 5.5 to 8.3 among six Salmonella strains. The results show that at 25°C some strains of each species are more resistant to pressure than the others. However, when one resistant and one sensitive strain from each species were pressurized at 345 MPa and 50°C, the population of all except the resistant S. aureus strain was reduced by more than 8 log cycles within 5 min. Viability loss of the resistant S. aureus strain was 6.3 log cycles even after 15 min of pressurization. This shows that strains of food-borne pathogens differ in resistance to hydrostatic pressure (345 MPa) at 25°C, but this difference is greatly reduced at 50°C. Pressurization at 50°C, in place of 25°C, will ensure greater safety of foods.